Start With Why how great leaders inspire every one to take action - Sinek, Simon (USA Portfolio, 2009)
Why are some people and organisations more innovative, more influential, and more profitable than others? Why do some command greater loyalty from customers and employees alike? Why are so few able to repeat their success over and over?
Keywords: Leadership